Energy assessment and environmental impact analysis of an R134a/R744 cascade refrigeration plant upgraded with the low-GWP refrigerants R152a, R1234ze(E), propane (R290) and propylene (R1270). (August 2019) - Sánchez, D.; Cabello, R.; Llopis, R.; Catalán-Gil, J.; Nebot-Andrés, L.
Highlights: Conversion of a direct R134a/R744 cascade to an indirect one is analysed energetically. Low-GWP100 refrigerants R152a, R1234ze(E), R290 and R1270 are also analysed. Indirect arrangement increases the energy consumption from +2.5% to +17.1%. The indirect arrangement reduces the refrigerant mass charge on average 58.5%. The environmental impact (TEWI) of the indirect arrangement is reduced by 30%. R152a is the best option for an indirect upgrading. Abstract: The European limitations associated with the use of fluorinated refrigerants have affected one of the most extended solutions used in commercial refrigeration in warm countries. Traditional cascade systems with R404A or R134a, in the high-temperature cycle, and R744 (CO2 ), in the low side, will be prohibited from 2022 onwards unless the refrigerants used have a GWP100 lower than 150. Since practically all the available refrigerants with low-GWP100 are flammable, a simple but effective modification can be adopted upgrading the current direct expansion system to an indirect one. Accordingly, the aim of this work is to determine the energy and environmental impact of converting an R134a/CO2 direct expansion cascade to an indirect one using the low-GWP100 refrigerants R152a, R1234ze(E), R290 and R1270. The experimental analysis is performed at three different heat rejection temperatures (from 23.3 to 43.6 °C), maintaining the cooling service product at temperatures of 2 °C and −20 °C on average.